Indicadores de processo da qualidade da assistência de enfermagem ao idoso na atenção primária - DIAS, Flávia Aparecida (2017)
Indicators are important aspects of service management. It reinforces the need to prioritize them in primary care. The objectives of this study were: to elaborate a conceptual model for the dimensions of nurses' work in primary care for the elderly; to convert the specific nurse attributions established by the Ministry of Health and the State Secretary of Health directed to the elderly health in primary care; to evaluate the face validity, terminology, content validity and the need for the proposed indicators; test the proposed indicators in relation to reliability; to evaluate the feasibility, utility and usability of the indicators. This is a methodological research, the steps being based on the development process by the National Database of Nursing Quality Indicators associated to the Agency for Healthcare Research and Quality, to know: literature review; development of the conceptual model; involvement of specialists; initial specification of candidate indicators; review panel, and; empirical analyzes. The documents selected concerned publications from 1994 to 2014.This project was approved by the Research Ethics Committee of the Federal University of Triangulo Mineiro, no. 1,058,438. The conceptual model identified specific conceptions of metaparadigms. Were built 21 indicators; after restatements totaled 22 indicators validated by the panel; all measures were considered appropriate, with valid content and agreement on terminology and need. The number of responses agreed by the evaluators in the 13 care indicators tested had a percentage of 93.3- 100%. Among the 22 indicators, only four indicators (borderline blood pressure and overweight / obesity) were evaluated as not available and not viable to be collected by both evaluators; with the exception of one indicator, the remaining considered available and feasible were highly recommended regarding the feasibility of collection. Only the indicator "monitoring the physical mobility of the elderly" obtained a negative answer as to the utility for quality of care. Were not considered useful fordetermining the receipt of financial incentives 13 indicators; in the evaluation of the usability of the indicator to compare the public reports between the Family Health Strategies (FHS) and the level of the geographic areas also obtained relatively low score, by state management, six indicators. Based on these data, this study ends with the recommendation of implementation of the 22 indicators: planning of activities directed to the elderly population; monitoring the health condition of the elderly; evaluation of health actions directed to the elderly population; coordination of the nursing team in the attention to the elderly; coordination of community health agents in care for the elderly; coverage of nursing consultation for the elderly; evaluation of the elderly in the nursing consultation; screening coverage for diabetes mellitus screening; coverage of the gynecological nursing consultation; evaluation of the elderly in the gynecological nursing consultation; appropriate vaccination for the elderly; use of the elderly carnet in nursing care; coverage of the nursing consultation to the elderly with diabetes mellitus; evaluation of the elderly with diabetes mellitus in the nursing consultation; coverage of the nursing consultation to the elderly with systemic arterial hypertension; evaluation of the elderly with systemic arterial hypertension in the nursing consultation; coverage of the nursing consultation for the elderly with overweight/obesity; evaluation of the elderly with overweight/obesity in the nursing consultation; coverage of the nursing consultation to the elderly with borderline blood pressure; evaluation of the elderly with borderline blood pressure at the nursing consultation; home care prescription 1; home visit in home care 1. These results may contribute to the management of care for the elderly by redirecting actions provided by the nurse in primary care.